Molecular regulation of skeletal muscle myosin heavy chain isoforms - Brown, David M. (2015)
Research investigating the regulation of muscle fibre type has traditionally been conducted in vivo, analyzing global changes at a whole muscle level. Broadly, this thesis aimed to explore more “molecular” approaches, utilizing molecular and cell biology to understand the expression and regulation of myosin heavy chain (MyHC) isoforms as an indicator of muscle fibre composition. The mRNA expression profile of six MyHC isoform genes during C2C12 myogenesis was elucidated to reveal that the C2C12 cell line mimics developing fast-twitch muscle fibres. Additional characterization of the C2C12 cell line revealed a dramatic restructuring of metabolic gene expression during the switch from proliferating to fully differentiated C2C12 muscle cells. Post-mitotic muscle cells exhibited increased glycolytic gene expression and reduced oxidative gene expression and an increase in gene expression of enzymes involved in redirecting glucose carbons into ATP generating pathways and away from macromolecule biosynthesis (p<0.01 for all genes). The dynamic plasticity of MyHC isoform gene expression was compared between C2C12 muscle cells and fully differentiated adult muscle. Exposure of adult muscle to the beta-adrenergic agonist, Ractopamine, induced dynamic transitions in MyHC isoform expression, from the IIA/IIX isoforms to increased IIB isoform expression (p<0.05 for all genes). An acute exposure of C2C12 muscle cells to Ractopamine was capable of inducing an exclusive and rapid induction of the MyHC IIB isoform gene expression during myogenesis (p<0.001). The C2C12 cell line was utilized as a host environment for a molecular-based approach to understand the role of the promoter sequence in regulating the species-differential induction of the MyHC IIB gene during myogenesis. A 3bp miss-match in the CArG-Ebox region (at -74bp, -68bp and -48bp) of the proximal MyHC IIB promoter was identified that dictates the differential expression of MyHC IIB in pigs and humans.